Calitz, T.M.L. 2019. Enhancing the Freedom to Flourish in Higher Education: Participation, Equality and Capabilities. Abingdon, Oxon: Routledge. - Abbas, Andrea (Critical Studies in Teaching and Learning, 2023)
Enhancing the Freedom to Flourish in Higher Education is the seventh book to be published in Routledge’s excellent, Society for Research into Higher Education Series, focusing on ‘the rapidly changing world of higher education, examined in a global context’, edited by Jennifer Case and Jeroen Huisman. Talita Calitz‘s important contribution to the series is based on a methodologically innovative and systematically theorised narrative study of eight South African undergraduates. The six female and two male undergraduates (seven black, one female from a mixed ethnic background) have racialbackgrounds that, statistical analysis suggests, would severely impair their chances of doing well in the South African system of undergraduate education. The theorised results of this participatory study produced insightfully complex and nuanced accounts of students’ experiences and outcomes. They illustrate how universities, in partnership with their students, are needed to transform the South African higher education system so that it helps black and coloured students, who are currently let down, to succeed. Calitz argues that the whole university system needs overhauling if universities are to make their contribution towards the transformation of wider society post-apartheid.